Empirical Insights into Digital Customer Retention: Technological Enablers and Strategic Applications - Muhammad Asif khan; Noor-UI Amin; Rino Subekti (Dinasti Publisher, 2025)
This research investigates customer retention strategies in the context of digital transformation, aiming to identify effective approaches through empirical investigations and rigorous statistical analyses. The study explores the roles of customer satisfaction, emotional attachment, trigger events, and perceived switching costs in influencing retention. Using surveys and regression analysis, data from diverse business sectors are analyzed to quantify these factors' impacts on customer loyalty. Results demonstrate that enhancing customer satisfaction, fostering emotional connections, and managing trigger events significantly improve retention rates. The findings contribute insights for businesses to optimize their retention efforts amidst digital advancements, offering actionable recommendations to strengthen customer relationships and sustain competitive advantage in contemporary markets.